Applications of mass spectrometry imaging to cancer - Drake, Richard R. (Advances in cancer research, 2017)
Front Cover -- Applications of Mass Spectrometry Imaging to Cancer -- Copyright -- Contents -- Contributors -- Preface -- References -- Chapter One: The Importance of Histology and Pathology in Mass Spectrometry Imaging -- 1. Importance of Pathology -- 2. Possible Errors Caused by Tissue Inherent Factors-Why Histology Is Important for Supervised Analysis -- 3. Possible Errors Caused by Sample Inherent Factors-Small Pretherapeutic Biopsies -- 4. Possible Errors Caused by Sample Preparations-Artifacts Are Not Your Friend -- 5. Possible Errors Caused by Ill-Defined Sample Groups in the Training Set-Keep It Black and White/Shades of Gray Are Not ... -- 6. Conclusion -- References -- Chapter Two: Applications of Mass Spectrometry Imaging to Cancer -- 1. Introduction -- 1.1. The Advantages of MSI -- 1.2. The Basic Principles of MSI -- 1.2.1. MALDI-TOF -- 1.2.2. MALDI-FT-ICR -- 1.2.3. SIMS-TOF -- 1.2.4. DESI -- 2. Protein MSI in Cancer Research -- 2.1. Distinguishing Tissue Types by Peptide MSI -- 2.2. Determining Tumor Margins by Peptide MSI -- 2.3. Prediction of Metastasis by Peptide MSI -- 2.4. Analysing Chemoresponse by Peptide MSI -- 2.5. Identification of Diagnostic and Prognostic Markers by Peptide MSI -- 2.6. Characterisation of Intra- and Intertumor Variability by Peptide MSI -- 2.7. Practical Considerations for Proteolytic Peptide MSI: Sample Preparation -- 2.8. Practical Considerations for Peptide MSI: Spatial Resolution -- 2.9. Practical Considerations for Peptide MSI: Mass Analysers -- 2.10. Practical Considerations for Peptide MSI: Identification -- 3. Lipid MSI in Cancer Research -- 3.1. Profiling Lipids in Cancer by DESI-MSI -- 3.2. Profiling Lipids in Cancer by SIMS-MSI -- 4. Glycan MSI in Cancer Research -- 5. Drug Imaging in Cancer Research -- 5.1. MALDI-MSI on Tissue Sections -- 5.2. MALDI-MSI on Whole Body Sections.